Analysis of the Implementation of Cultural Preservation Poli-cies in the Management of the Huma Betang Eka Tingang Nganderang Tourist Destination in Palangka Raya City - Gladys Abigail; Frillia Damayanti; Felicitya Navida; Keysha Destriana (Institut Nalanda, 2026)
Cultural-based tourism has increasingly become an important strategy in regional development, particularly in preserving local cultural heritage while supporting the growth of the tourism sector. This study aims to analyze the implementation of cultural preservation policies in the management of the Huma Betang Eka Tingang tourist destination in Palangka Raya City and to identify the factors influencing policy effectiveness. This research employs a qualitative method with a literature study approach by examining various written sources, including books, scientific journals, government regulations, and related documents relevant to cultural preservation and cultural tourism management. The data analysis technique follows the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The findings show that the implementation of cultural preservation policies in Huma Betang Eka Tingang is influenced by four main factors: policy communication, resource availability, implementer disposition, and bureaucratic structure. Although policy communication has been conducted through cultural promotion programs and events, coordination among stakeholders remains suboptimal. Limited human resources and budget constraints also affect program effectiveness.